Effect of propelling surface size on the mechanics and energetics of front crawl swimming - Toussaint, H. M.; Janssen, T.; Kluft, M. (Journal of Biomechanics, 1991)
In swimming the propulsive force is generated by giving a velocity change to masses of water. In this process energy is transferred from the swimmer to the water, which cannot be used to propel the swimmer. Theoretical considerations indicated that an increase of the propelling surface size should lead to a reduced loss of energy to the water. Thus, in this study, the effect of artificially enlarging the propelling surface of the hand was examined. The effect was examined in terms of the propelling efficiency during front crawl swimming using the arms alone. The legs were Boated with a small buoy as previously described (Toussaint et al., J. appl. Physiol., 65, 2506-2512, 1988a). In ten competitive swimmers (six male, four female) the rate of energy expenditure (power input), power output, work per stroke cycle, distance per stroke cycle, work per unit distance, and propelling efficiency, were determined at various swimming speeds once with and once swimming without paddles. At the same average velocity the effect of swimming with paddles was to reduce P, POa, nd Ad by 6,7.6, and 7.5 % respectively, but to increase er and A, by 7.8 and 7 %. The increase in distance. per stroke cycle and the decrease in stroke cycle frequency matched the predicted values based on the theoretical considerations in which the actual increase in propelling surface size was taken into account.